RECENT GOVERNMENTAL ACCOUNTING PUBLICATIONS. - Read, W. H. (The Accounting Review, 1943)
Abstract This article focuses on the recent accounting publications by the U.S. Government. Some of the published books are "Municipal Budget Procedure and Budgetary Accounting," "Work Measurement in the City of Los Angeles Building and Safety Departments," "Governmental Cost Accounting in the Los Angeles Area" and "Cost Accounting and Work Measurement in the Federal Government." Most of the text is devoted to a discussion of budgeting for the general fund. However, budgeting for the other usual municipal funds is treated briefly with a three page discussion being given to capital budgeting in the first book. General fund budgeting is presented in the traditional three phases, namely, preparation, adoption, and execution. In the three chapters devoted to budget preparation the importance of the work program as being the basis of expenditure estimates is well brought out. A model work program is presented in the appendix. Most works on budgeting recommend the "accrual basis." Others advocate the "cash basis." This bulletin not only describes detailed procedures under both of the traditional bases but presents a very practical method of budgeting revenues on a "cash basis" and expenditures on an "accrual basis."